2020
DOI: 10.1111/1750-3841.15029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different thawing methods on physicochemical properties and structure of largemouth bass (Micropterus salmoides)

Abstract: To evaluate the physicochemical properties and structure of thawed fillets, following six treatments were used: conventional thawing, microwave thawing, microwave or ultrasound combined with vacuum thawing, magnetic nanoparticles combined with microwave or far‐infrared thawing. The thawing loss, cooking loss, pH, color, texture change, water‐holding capacity, and water migration of fish fillets were determined. The total volatile base nitrogen and thiobarbituric acid were used to determine the degree of protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…2(A), the hardness value of the MT group was significantly higher than that of fresh samples and other groups (P \ 0.05), and there was no significant difference in the hardness value of the other groups, which may be caused by overheating in the microwave caused the oxidation and aggregation of fish protein (Wang et al, 2020a). Cai et al (2020) also found a similar phenomenon after thawing frozen largemouth bass. The hardness of microwave thawed fillets is harder than other thawing methods.…”
Section: Texturementioning
confidence: 77%
“…2(A), the hardness value of the MT group was significantly higher than that of fresh samples and other groups (P \ 0.05), and there was no significant difference in the hardness value of the other groups, which may be caused by overheating in the microwave caused the oxidation and aggregation of fish protein (Wang et al, 2020a). Cai et al (2020) also found a similar phenomenon after thawing frozen largemouth bass. The hardness of microwave thawed fillets is harder than other thawing methods.…”
Section: Texturementioning
confidence: 77%
“…All samples had higher TVB-N values after freezing and thawing due to a mass of basic volatile compounds produced by the degradation of protein and nonprotein nitrogen compounds including ammonia, trimethylamine, methylamine, and dimethylamine [25] . The lower the TVB-N value is, the less tyrosine and methionine are destroyed in the protein, which means that the nutrients are better protected [29] . Therefore, these results indicated that the UAT samples showed less protein degradation and less nutritional loss than the AT and FWT samples.…”
Section: Resultsmentioning
confidence: 99%
“…Among the different thawing methods, microwave thawing required the shortest time, which can produce high thawing temperature and inhibit the growth of bacteria. However, it could cause local overheating and reach protein denaturation temperature easily (Cai et al, 2020). For ultrasound thawing, one could select the frequency to avoid the local high temperature and decrease the possibility of water loss (Li et al., 2018), but, the poor penetration, localized heating, and high consumption of power are the shortcomings of ultrasound thawing (Cai et al., 2018).…”
Section: Introductionmentioning
confidence: 99%